2005
DOI: 10.1038/sj.hdy.6800678
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the petal shape variation in Primula sieboldii caused by breeding process in the last 300 years

Abstract: Primula sieboldii (E. Morren) has been a popular garden plant at least since the Edo period, about 300 years ago. We compared petal form between cultivars and wild populations in order to characterise the changes that have occurred during domestication. The comparison was made using EF-PCA analysis, which describes overall petal shape mathematically by transforming petal contour coordinates into elliptic Fourier descriptors; it subsequently summarises these descriptors by principal component analysis (PCA). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 19 publications
0
34
1
Order By: Relevance
“…Such a framework should incorporate allometric relationships, as changes in size are often accompanied by changes in shape (1), reflecting an interaction between developmental and selective constraints. Much progress has been made in quantifying shape or size variation between species, ecotypes, and varieties by using numerical methods (2)(3)(4)(5)(6), and in some cases genes underlying this variation have been defined by QTL analysis (7)(8)(9). However, so far, these approaches have not been combined to allow variation between a range of species to be placed in a genetic context.…”
mentioning
confidence: 99%
“…Such a framework should incorporate allometric relationships, as changes in size are often accompanied by changes in shape (1), reflecting an interaction between developmental and selective constraints. Much progress has been made in quantifying shape or size variation between species, ecotypes, and varieties by using numerical methods (2)(3)(4)(5)(6), and in some cases genes underlying this variation have been defined by QTL analysis (7)(8)(9). However, so far, these approaches have not been combined to allow variation between a range of species to be placed in a genetic context.…”
mentioning
confidence: 99%
“…For instance, floral organs can be photographed or scanned and their size and shape analyzed by using various image software packages. DIAS of traits, such as standard length, width, area, and perimeter, facilitates extensive and detailed phenotypic analyses to describe subtle differences in flower size (Yoshioka et al 2004(Yoshioka et al , 2005. Appropriate software packages can provide more accurate, consistent, and objective measurement for floral traits, such as style length, ovary style angle (for assessment of the mechanical fit to pollinator) or pollen presentation that were impossible or impractical to determine manually (Suso et al 2005a).…”
Section: Key Aspects Of Floral Traits For Improving Cprmentioning
confidence: 99%
“…Our results also suggested that other cultivars originated from the wide floral variation in the Saitama population. With regard to genetic variation in the depth of the head notch (PC1), Yoshioka et al (2005) showed that wild P. sieboldii had a deeper head notch than cultivars; the shallower head notch may have resulted from previous breeding manipulations, such as crossing and selection. Currently, none of the more than 300 P. sieboldii cultivars have a deep head notch.…”
Section: Molecular Versus Quantitative Genetic Variationmentioning
confidence: 99%